2019
DOI: 10.1152/ajpregu.00379.2018
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in metabolic fuel use coincide with maximal rates of ventilation and body surface rewarming in an arousing hibernator

Abstract: It is well established that hibernating mammals rely predominantly on lipid stores to fuel metabolism throughout the hibernation season. However, it is unclear if other endogenous fuels contribute to the rapid, ~400-fold increase in metabolic rate during the early phase of arousal from torpor. To investigate this issue, we used cavity ring-down spectroscopy, a technique that provides a real-time indication of fuel use by measuring the ratio of 13C to 12C in the exhaled CO2 of arousing 13-lined ground squirrels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…One reason for this could be regional temperature differences during rewarming. 61 , 62 Tissues were collected 2 hours after IV bolus infusion during arousal; the head and thoracic region of the body warms more quickly than distal regions partially due to proximity of brown adipose tissue deposits and distal vasoconstriction. 61 Further, in AGS arousal, blood flow to the extremities significantly lags behind brain and organ blood flow, meaning that metabolic exchanges with circulation occur more quickly for the brain and visceral tissues than for the quadriceps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this could be regional temperature differences during rewarming. 61 , 62 Tissues were collected 2 hours after IV bolus infusion during arousal; the head and thoracic region of the body warms more quickly than distal regions partially due to proximity of brown adipose tissue deposits and distal vasoconstriction. 61 Further, in AGS arousal, blood flow to the extremities significantly lags behind brain and organ blood flow, meaning that metabolic exchanges with circulation occur more quickly for the brain and visceral tissues than for the quadriceps.…”
Section: Discussionmentioning
confidence: 99%
“… 61 , 62 Tissues were collected 2 hours after IV bolus infusion during arousal; the head and thoracic region of the body warms more quickly than distal regions partially due to proximity of brown adipose tissue deposits and distal vasoconstriction. 61 Further, in AGS arousal, blood flow to the extremities significantly lags behind brain and organ blood flow, meaning that metabolic exchanges with circulation occur more quickly for the brain and visceral tissues than for the quadriceps. 62 If experiments had taken place during full arousal (T b >34°C) for a longer duration, we might have seen higher incorporation of labeled 15 N in all tissues and peripheral skeletal muscle that lags in rewarming.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the energetically expensive arousals from torpor is not known, although, at least in lemurs, they appear to be compelled only in animals exhibiting torpid Tb < 30 • C (Dausmann et al, 2004). Clearly rates of biochemical reactions slow as Tb decreases during torpor, and differences in the thermal sensitivity of various reactions throughout the body leads to widespread changes, both increases and decreases, in the relative abundances of metabolites, transcripts and proteins across the torpor bout; the short, warm arousal periods are also highly dynamic, with changes between initial rewarming through the beginning of cooling when the next bout of torpor begins (Nelson et al, 2009;Epperson et al, 2011;Hindle et al, 2011Hindle et al, , 2014Jani et al, 2012;Grabek et al, 2015a;Bogren et al, 2017;D'Alessandro et al, 2017;Regan et al, 2019;Rice et al, 2020). While rewarming restores the slowed cellular processes and biochemical reaction rates of torpor in every system in the body, the detailed molecular mechanisms orchestrating these dynamics remain to be fully elucidated (see van Breukelen and Martin, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the increase in T b up to 12–16°C is accompanied by an increase in RQ to 1.0, indicating oxidation of carbohydrates, mainly by muscles for shivering thermogenesis (Mokrasch et al, 1960 ; Castex and Hoo-Paris, 1987 ; Heldmaier et al, 2004 ), and/or an evacuation of the CO 2 accumulated during torpor (Malan et al, 1988 ). A recent study has deepened the analysis in hibernating thirteen-lined ground squirrels (Regan et al, 2019 ). It has shown that a combination of lipids and carbohydrates is used during the initial ~60 min of arousal before switching to predominantly lipid oxidation.…”
Section: Maintenance Of Lean Body Mass In Hibernators During Wintermentioning
confidence: 99%